Exploring the Medical Knowledge Presented in the Quran: An Analysis of its Accuracy and Relevance - Saleem, Sheikh Mohd; Jan, Shah Sumaya (Universitas Islam Indonesia, 2023)
The Quran, the holy book of Islam, contains several references to medical concepts and practices. This study aims to review and analyze the medical knowledge presented in the Quran and its relevance in modern medicine. To this end, a comprehensive literature review was conducted to identify all the medical concepts discussed in the Quran. The accuracy and relevance of these concepts in light of modern medical knowledge were evaluated through critical analysis of current literature. The study found that the Quran contains references to several medical concepts, including disease prevention, hygiene, and healthy living. These concepts are still relevant and applicable in modern medicine. The Quranic emphasis on the importance of faith and prayer in healing, however, may not be sufficient in modern medical practice. While the medical knowledge presented in the Quran has been praised for its accuracy and relevance, it is important to recognize that the Quran was revealed during a specific time and cultural context. There may be some limitations to the medical knowledge presented in the Quran when viewed through a modern lens. The study thus concludes that the Quranic medical knowledge has made significant contributions to the development of medical knowledge and practices. However, it is important to view its teachings in the context in which they were presented and to consider the limitations of these teachings when applying them to modern medical practice.